Studies on Structural, Spectral, and Optical Properties of Organic Nonlinear Optical Single Crystal: 2-Amino-4, 6-dimethylpyrimidinium p-Hydroxybenzoate. (28th March 2013) - Sudhahar, S.; Krishna Kumar, M.; Silambarasan, A.; Muralidharan, R.; Mohan Kumar, R.
Abstract : 2-Amino-4, 6-dimethylpyrimidinium p-hydroxybenzoate (ADPHB), a novel organic material, was synthesized, and crystals were grown by slow evaporation solution growth method. The cell parameters and crystalline perfection of the grown crystal were studied by single crystal and powder X-ray diffraction analyses. The presence of various functional groups of the grown crystal was confirmed using Fourier Transform infrared spectral analysis. UV-Visible spectrum shows that ADPHB crystals have high transmittance in the range 305–900 nm. The refractive index and transient photoluminescence properties of the grown crystal were analyzed. The laser induced surface damage threshold, optical birefringence, and second harmonic generation efficiency of the grown crystal were studied.